Features of the ribbon-flag culture of Shamanistic-Buddhist regions of Eurasia - Lamazhaa Чимиза (Turkic Studies Journal, 2024)
The article analyzes the characteristics of the ribbon-flag culture, which emerged in the regions where the Shamanistic cultures of the steppe and mountainous steppe of the Sayano-Altai area (the territory stretching from Lake Baikal in Southern Siberia to Western Mongolia) merged with Buddhist-Tibetan traditions. The author proposes considering it as a part of the larger area of ribbon culture within shamanism in Eurasia. To define the term ‘ribbon-flag culture’, the author provides several factors that characterize this culture. The author conducted direct research on the ribbon-flag culture in one of its regions, shamanistic-Buddhist Tuva, over the past two decades. The analysis of sources and our own materials leads us to the conclusion that the overall trajectory of the development of the tradition of ribbon flag culture can be traced back to the animistic and pre-shamanistic beliefs and ritual practices of the nomadic people of the Sayano-Altai region in Inner Asia. This tradition was further strengthened by the shamanistic ritual practices that developed in the region, including among the Tibetan nomads. Subsequently, it was enriched by cultural influences from India and China, such as Buddhism.